Comparative effectiveness of interventions for improving adherence to ocular hypotensive therapy in patients with glaucoma or ocular hypertension: protocol for network meta-analysis - Young Kook Kim; Ahnul Ha; Mirinae Jang; Sung Ryul Shim (BMJ Open)
Introduction Poor medication adherence is an important issue in healthcare. Various types of interventions for improved adherence to ocular hypotensive therapy have been proposed, though evidence on the effectiveness of any isolated intervention remains limited. The current protocol is an ongoing network meta-analysis (NMA) design that enables comparative investigation of any and all interventions for which there are available randomised controlled trials (RCTs). Our aim is the systematic comparison of the efficacy of different types of adherence interventions for patients suffering from glaucoma or ocular hypertension (OHT).Methods and analysis Studies of interest will assess the effects of any interventions on medication adherence in adults (age ≥18 years) with either glaucoma or OHT. Four electronic databases (Cochrane Central Register of Controlled Trials, Embase, MEDLINE and Scopus) will be searched for RCTs published in any language, without any time limitation. First, titles and abstracts, and then full-text papers, will be screened by two reviewers, who will extract the useful data. The primary outcome measure is an intervention’s impact on adherence. The two reviewers will also assess, using the relevant domain-based risk-of-bias assessment tool, the internal validity of the studies. The overall quality of the evidence will be assessed by the Confidence in Network Meta-Analysis approach, and will be summarised with network diagrams. To allow for assessment of both direct and indirect evidence, a contribution matrix will be used. For visualisation of the effects of all of the included interventions, forest plots will be constructed. Pairwise effect sizes will be calculated according to all of the evidence available in the network.Ethics and dissemination This work will synthesise evidence from already published studies and, as such, will not require an ethics review or approval. A manuscript presenting the findings will be submitted to a peer-reviewed scientific journal for publication.PROSPERO registration number CRD42021253145.